2020
DOI: 10.1007/s00468-020-01956-1
|View full text |Cite
|
Sign up to set email alerts
|

Intra-annual density fluctuations (IADFs) inPinus nigra(J. F. Arnold) at high-elevation in the central Apennines (Italy)

Abstract: Although wood anatomical features can provide yearly resolved climatic information at sub-seasonal resolution, the occurrence of intra-annual density fluctuations (IADFs) might be triggered by several abiotic factors under different ecological settings. Here, we use information on cambial age and tree-ring width to standardize the frequency of IADFs in European black pines from three different mountain slopes in the central Apennines (Italy). At each site, we sampled isolated 15-30year pioneer pines above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…IADFs were frequently observed in tree rings of pine trees, with a higher frequency on limestone. It has been reported that severe conditions during the growing season, such as shortage of water, may trigger the formation of IADFs (de Luis et al, 2007;Piermattei et al, 2020). The site on limestone is more sensitive to water stress due to lower water retention capability as indicated from narrower wood increments in both species and a more pronounced response to unfavorable growing conditions was observed in pine through appearance of IADFs.…”
Section: The Relationship Between Wood Structure and Wood Densitymentioning
confidence: 99%
“…IADFs were frequently observed in tree rings of pine trees, with a higher frequency on limestone. It has been reported that severe conditions during the growing season, such as shortage of water, may trigger the formation of IADFs (de Luis et al, 2007;Piermattei et al, 2020). The site on limestone is more sensitive to water stress due to lower water retention capability as indicated from narrower wood increments in both species and a more pronounced response to unfavorable growing conditions was observed in pine through appearance of IADFs.…”
Section: The Relationship Between Wood Structure and Wood Densitymentioning
confidence: 99%
“…However, IADFs have attracted increasing attention over the last two decades because they reflect variations in climatic conditions during the growing season, and can therefore be used as proxies of past environmental conditions with intra-annual resolution 11 , 16 18 . To date, studies focusing on IADFs formation have mainly been concentrated within the western Mediterranean basin, and have focused primarily on the genus Pinus and a few other gymnosperms 11 , 16 , 18 22 . A smaller number of studies have focused on angiosperms, such as Arbutus unedo , Erica arborea and Quercus ilex 2 , 23 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The frequency and formation of IADFs in tree rings depend on tree age and size, or ring width (e.g., Novak et al 2013;Nabais et al 2014;Campelo et al 2015;Piermattei et al 2020).…”
mentioning
confidence: 99%